Joint optimization of relay-precoders and decoders with partial channel side information in cooperative networks - Yi, Zhihang; Kim, Il-min (IEEE journal on selected areas in communications, 2007)
We jointly optimize the relay-precoders and decoders with full or partial channel side information (CSI) in a cooperative network. Specifically, three different CSI assumptions are considered: 1) full CSI at the destination terminal and the relay terminals; 2) full CSI at the destination terminal and partial CSI at the relay terminals; 3) partial CSI at the destination terminal and the relay terminals. We show that, under the assumption of full CSI at the destination terminal and the relay terminals, the optimum relay-precoder is the cooperative transmission beamforming and the optimum decoder is a maximum ratio combiner. Under the two partial CSI assumptions, the optimum relay-precoders and decoders work in a fashion of channel selection. It is demonstrated that the proposed optimum relay-precoders and decoders improve the performance considerably